PERANCANGAN GAME EDUKASI CALCUBOY PADA ANAK USIA 4 SAMPAI 7 TAHUNSTUDI KASUS : TK DHARMA WANITA 1 TAROKAN DAN SDN TAROKAN 1 - Bagus Iswanto, Bima; Wahyu Widodo, Danang; Nur Farida, Intan (Nusantara of Engineering (NOE), 2024)
This research explores the development and implementation of the educational game "Calcuboy: Math Adventure" for children aged 4-7 as a counting learning tool. A case study was conducted at TK Dharma Wanita 1 Tarokan and SDN Tarokan 1. The implementation, based on the Game Design Document (GDD), focused on the High Concept Document (HCD) and Character Design Document (CDD). The evaluation of the implementation involved game testing with 20 children aged 4-7 as respondents. The analysis included character control ease, game difficulty level, counting challenges, responses to graphics and sound, emotional engagement, and learning experience. The results show that 75% of respondents found it easy to control the character Aiden, while 25% considered it difficult. Most (70%) assessed that the difficulty level was not suitable for the children's age, and 60% responded negatively to counting challenges. Responses to graphics and sound tended to be positive (55%), but 45% gave negative or neutral feedback. Children's emotional engagement was low (75%), with only 25% feeling involved. Positive learning experiences were reported by 40% of respondents, while 60% stated otherwise. The conclusion indicates the potential of the game as a counting learning tool but highlights the need for improvements, such as adjusting difficulty levels, developing graphic and sound aspects, and enhancing emotional engagement with the character Aiden.